Oncogenic K-Ras upregulates ITGA6 expression via FOSL1 to induce anoikis resistance and synergizes with αV-Class integrins to promote EMT - Zhang, K (Oncogene, 2017)
In many cancer types, integrin-mediated signaling regulates proliferation, survival and invasion of tumorigenic cells. However, it is still unclear how integrins crosstalk with oncogenes to regulate tumorigenesis and metastasis. Here we show that oncogenic K-Ras(V12) upregulates α6-integrin expression in Madin–Darby canine kidney (MDCK) cells via activation of the mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK)/Fos-related antigen 1-signaling cascade. Activated α6-integrins promoted metastatic capacity and anoikis resistance, and led to perturbed growth of MDCK cysts. Transcriptomic analysis of K-Ras(V12)-transformed MDCK cells also revealed robust downregulation of αV-class integrins. Re-expression of αV-integrin in K-Ras(V12)-transformed MDCK cells synergistically upregulated the expression of Zinc finger E-box-binding homeobox 1 and Twist-related protein 1 and triggered epithelial-mesenchymal transition leading to induced cell motility and invasion. These results delineate the signaling cascades connecting oncogenic K-Ras(V12) with α6- and αV-integrin functions to modulate cancer cell survival and tumorigenesis, and reveal new possible strategies to target highly oncogenic K-Ras(V12) mutants.